2020
DOI: 10.1007/s11606-020-06120-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Patients Who Return to Hospital Following Discharge from Hospitalization for COVID-19

Abstract: BACKGROUND: Data on patients with coronavirus disease 2019 (COVID-19) who return to hospital after discharge are scarce. Characterization of these patients may inform post-hospitalization care. OBJECTIVE: To describe clinical characteristics of patients with COVID-19 who returned to the emergency department (ED) or required readmission within 14 days of discharge. DESIGN: Retrospective cohort study of SARS-COV-2positive patients with index hospitalization between February 27 and April 12, 2020, with ≥ 14-day f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
113
7
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(143 citation statements)
references
References 18 publications
19
113
7
4
Order By: Relevance
“… 3 , 4 , 5 The readmission rate of 5.2% observed in our study is within the range of other reports. 3 , 13 , 14 , 15 …”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 , 5 The readmission rate of 5.2% observed in our study is within the range of other reports. 3 , 13 , 14 , 15 …”
Section: Discussionmentioning
confidence: 99%
“…Other reasons for readmission included: pain, altered mental status, falls, fever, soft tissue infection, thrombotic events and gastrointestinal symptoms 3‐8 . A retrospective study from New York demonstrated that among comorbidities, chronic obstructive pulmonary disease (COPD), immunosuppression and hypertension are associated with increased risk for readmission 6 . A case‐control study from Spain confirmed the immunosuppression as a risk factor, whereas did not find an association with COPD 3 .…”
Section: Introductionmentioning
confidence: 99%
“…A case‐control study from Spain confirmed the immunosuppression as a risk factor, whereas did not find an association with COPD 3 . However, both studies showed that a shorter length of stay is increasing the risk for hospital return 3,6 . Fever within 48 hours prior to discharge, and insufficient anticoagulation during index admission were also reported as potential risk factors for readmissions 3,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19) is a complex clinical illness with potential complications that might require ongoing clinical care ( 1 3 ). Few studies have investigated discharge patterns and hospital readmissions among large groups of patients after an initial COVID-19 hospitalization ( 4 7 ). Using electronic health record and administrative data from the Premier Healthcare Database, * CDC assessed patterns of hospital discharge, readmission, and demographic and clinical characteristics associated with hospital readmission after a patient’s initial COVID-19 hospitalization (index hospitalization).…”
mentioning
confidence: 99%